Attenuation of amyotrophic lateral sclerosis via stem cell and extracellular vesicle therapy: An updated review - Gavin Lockard; Jonah Gordon; Samantha Schimmel; Bassel El Sayed; Molly Monsour; Svitlana Garbuzova‐Davis; Cesar V. Borlongan (Neuroprotection)
Abstract Amyotrophic lateral sclerosis (ALS) is a rapidly fatal neurological disease characterized by upper and lower motor neuron degeneration. Though typically idiopathic, familial forms of ALS are commonly composed of a superoxide dismutase 1 (SOD1) mutation. Basic science frequently utilizes SOD1 models in vitro and in vivo to replicate ALS conditions. Therapies are sparse; those that exist in the market extend life minimally, thus driving the demand for research to identify novel therapeutics. Transplantation of stem cells is a promising approach for many diseases and has shown efficacy in SOD1 models and clinical trials. The underlying mechanism for stem cell therapy presents an exciting venue for research investigations. Most notably, the paracrine actions of stem cell‐derived extracellular vesicles (EVs) have been suggested as a potent mitigating factor. This literature review focuses on the most recent preclinical research investigating cell‐free methods for treating ALS. Various avenues are being explored, differing on the EV contents (protein, microRNA, etc.) and on the cell target (astrocyte, endothelial cell, motor neuron‐like cells, etc.), and both molecular and behavioral outcomes are being examined. Unfortunately, EVs may also play a role in propagating ALS pathology. Nonetheless, the overarching goal remains clear: to identify efficient cell‐free techniques to attenuate the deadly consequences of ALS.